Pandangan Tokoh Rifa’iyah dan Nahdhatul ‘Ulama tentang Pembaharuan Akad Nikah Di Kalangan Jam’iyah Rifa’iyah Dukuh Paesan Kecamatan Kedungwuni Kabupaten Pekalongan - Rizqa Nufa, Ellora (Al-Hukkam: Journal of Islamic Family Law, 2022)
Tajdid marriage or renewing the marriage contract is a tradition carried out by Jam'iyah Rifa'yah. This study examines the marriage contract among the Jam'iyyah Rifa'iyah Hamlet of Paesan West Kedungwuni Village, Kedungwuni District, Pekalongan Regency and the views of Rifa'iyah leaders regarding the implementation of the marriage contract among the Jam'iyyah Rifa'iyah Hamlet of Paesan Village, West Kedungwuni District, Kedungwuni Regency. Pekalongan views and figures from Nahdhatul 'Ulama regarding the implementation of the marriage contract among the Jam'iyyah Rifa'iyah Hamlet of Paesan, Kedungwuni Barat Village, Kedungwuni District, Pekalongan Regency. marry. Jam'iyah Rifa'iyah Dukuh Paesan tries not to carry out the tajdid marriage tradition because it considers marriages carried out today to meet the stipulated conditions and to save time and energy. The marriage has been handed over to the Kyai and the task of the penghulu is only as VAT (Marriage Registrar) only. Whereas in the NU jam'iyah from ancient times until now the marriage contract is only carried out once, there is no implementation of tajdid marriage as in the Rifa'iyah group. This means that in terms of the marriage contract, Rifa'iyah and Nahdhatul Ulama are almost the same, there is no difference that makes the implementation of tajdid marriage today.